Jumper - Milchan, Arnon, 1944-; Kinberg, Simon; Goyer, David S.; Uhls, Jim, 1961-; Liman, Doug.; Christensen, Hayden, 1981-; Jackson, Samuel L.; Lane, Diane; Bell, Jamie, 1986-; Bilson, Rachel; Rooker, Michael, 1955-; Hulce, Tom, 1953-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
David is a Jumper who can teleport himself anywhere in the world, which creates a fun and exciting life. Things turn deadly when David finds himself pursued by a secret organization sworn to kill Jumpers. He forms an uneasy alliance with another Jumper and becomes a player in a war that has been raging for thousands of years.
Title from disc surface.
Based on the novel by Steven Gould.
Special features: Audio commentary by director Doug Liman; "Jumping from novel to film" featurette; "Making an actor Jump" featurette; "Previz: future concepts" featurette.
Director of photography, Barry Peterson ; editors, Saar Klein, Dean Zimmerman, Don Zimmerman ; music, John Powell ; costume designer, Magali Guidasci ; production designer, Oliver Scholl ; special effects supervisor, Yves De Bono ; visual effects supervisors, Joel Hynek, Colin Strause, Greg Strause.
Hayden Christensen, Samuel L. Jackson, Diane Lane, Jamie Bell, Rachel Bilson, Michael Rooker, Tom Hulce, Kristen Stewart, Teddy Dunn, Annasophia Robb, Max Thieriot.
MPAA rating: PG-13; for sequences of intense action violence, some language and brief sexuality.
Keywords: Rice, Davy (Fictitious character) -- Fiction; Teleportation -- Drama; Secret societies -- Drama; Alliances -- Drama; Man-woman relationships -- Drama; Fathers and sons -- Drama; Feature films; Science fiction films; Suspense films; Action and adventure films; Video recordings for the hearing impaired